The Institutional and Policy Environment and the Quest for Industrialization in Nigeria - Iyoboyi, Martins; Muftau O., Olarinde; S. Ademola, Abdulsalam (Journal of Economics and Behavioral Studies, 2016)
The paper empirically investigates the impact of the institutional and policy environment on Nigeria’s industrialization, using annual data for the period 1981 to 2013. The institutional environment was proxied by quality of service delivery while government expenditure as a percentage of GDP and real exchange rate were used to reflect the policy environment. Foreign direct investment as percentage of GDP was employed to reflect technological transfer and diffusion. Using the technique of cointegration, a long run relationship was found between industrialization and associated variables. Government expenditure was found to be positively related to industrialization and statistically significant in the long and short run. In the short run, real exchange rate is positively related to industrialization and statistically significant, while a negative and statistically significant relationship was found in the long run. In the long and short run, technological transfer indicates a negative relationship with industrialization. Quality of service delivery was found to influence industrialization positively and significantly in the long and short run. A bilateral causality was found between industrialization and the associated variables. Based on the empirical findings, it is concluded that the institutional and policy environments are critical to industrialization in Nigeria and that pragmatic efforts should be made to initiate and implement policies that promote industrial growth, while enhancing the quality of institutions.